PENGEMBANGAN UMKM SERTA PENGABDIAN DI BIDANG PENDIDIKAN DAN KESEHATAN DI DESA LANGKO - Hidayat, Rahmat; Wirawan, Devitha Octaviana; Sulastri, Eva; Atikasari, Atikasari; Zakhrah, Siti; Oktaviana, Putri; Yusri, Diah Laili; Fatrani, Baiq Nuinsa Sohi; Febianingsih, Rahmiana; Safitri, Nadya (Jurnal Wicara, 2023)
Real Work Lecture (KKN) is a form of community service activity carried out by tertiary institutions. In the KKN activities carried out in Langko Village, Lingsar District, West Lombok Regency. Student groups carry out activities with the aim of developing village potential. The purpose of carrying out this activity is to develop the potential that exists in the village such as palm sugar and banana-cassava chips as well as carry out services in the fields of education and health. The method used is palm sugar to palm ant sugar, flavors of banana and cassava chips, socialization on prevention of early marriage, clean Friday, healthy Saturday, teaching at tpq, calistung, teaching at school. The results obtained were to help develop the business of making palm ant sugar, increase the reading and numeracy skills of school students, outreach to prevent early marriage, CALISTUNG for the elderly so that they still know letters and numbers can also read and write, help teach the Koran TPQ, Friday is clean so that friendly relations were established by working together, developing a chip business by providing flavor variants and updating packaging and also healthy Saturdays were carried out so that residents in Langko village could maintain good friendships. Apart from that, the Mataram University Integrated KKN group is also involved in various other activities, namely helping prepare food for pregnant women in Langko Village as well as delivering it to their respective homes, posyandu activities and cleaning the village environment. The results of the activities above show that the activities of the Mataramini University Integrated KKN Group have carried out several work programs for the potential that exists in Langko Village related to mapping village potential and developing existing potentials in the fields of MSME, education and health.